2002
DOI: 10.1185/030079902125000336
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Therapeutic Efficacy of 4-Methylpyrazole andN-Acetylcysteine on Acetaminophen (Paracetamol) Hepatotoxicity in Rats

Abstract: Obtaining effective analgesia with a minimal erosive effect on gastric mucosal tissue has increased the consumption of acetaminophen (paracetamol), especially among the elderly. However, the hepatotoxic effects of acetaminophen have also increased. We aimed to compare the effects of 4-methylpyrazole (4-MP), N-acetylcysteine (NAC) and their combined use on the hepatotoxicity of acetaminophen in a rat model. Male Wistar Albino rats were divided into six groups. Groups 1-5 received 2,000 mg/kg acetaminophen by ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2003
2003
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…4,10 4MP (Sigma-Aldrich, St. Louis, MO) was dissolved in saline and was co-administered with APAP at a dose of 50 mg/kg as used in previous studies. 36,37 Five mice were used per group for each intervention and time point. The animals were euthanized under isoflurane anesthesia 30 min or 6 h post-APAP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,10 4MP (Sigma-Aldrich, St. Louis, MO) was dissolved in saline and was co-administered with APAP at a dose of 50 mg/kg as used in previous studies. 36,37 Five mice were used per group for each intervention and time point. The animals were euthanized under isoflurane anesthesia 30 min or 6 h post-APAP.…”
Section: Methodsmentioning
confidence: 99%
“…29 Although 4MP is a competitive inhibitor of alcohol dehydrogenase, 3032 and as such is clinically used as an antidote to methanol and ethylene glycol poisoning, 33 studies with human microsomes and HepG2 cells have demonstrated that 4MP can also inhibit CYP2E1 34,35 In addition, 4MP attenuated APAP-induced liver injury in rats 36,37 but appeared to be not more effective than NAC. 37 However, there are some concerns with these animal studies. First, use of a rat model is problematic as excessive doses of APAP are being used resulting in limited necrosis, which questions the relevance of this model for human patients.…”
Section: Introductionmentioning
confidence: 99%
“…4-MP is a competitive antagonist of alcohol dehydrogenase and a potent CYP450 2E1 inhibitor that is used in the treatment of ethylene glycol and methanol toxicity. 4-MP has been studied as an alternative to NAC in rats with APAP-induced hepatotoxicity by Küçükardalı et al The authors compared the efficacy of NAC and 4-MP alone and in combination, ultimately concluding that the two xenobiotics have similar efficacy in limiting hepatotoxicity, as reflected by lower levels of serum transaminases and lesser degrees of hepatic necrosis [9]. In addition, a recent study by Akakpo et al investigated the protective effect of 4-MP alone in treatment of APAP-induced liver injury in both mice and primary human hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Paracetamol is excreted as sulfate and glucuronide conjugation and some of it is converted to n acetyl-β-benzoquinone imine (NAPQI), a reactive metabolite, which is formed during the metabolism of paracetamol in the cytochrome P450 system in the liver. 3,4 However, many studies have shown that high dose or frequent use of paracetamol lead to damage to various tissues, particularly in liver and kidney. [5][6][7][8] Furthermore, its toxicity potential has not yet been fully established.…”
Section: Introductionmentioning
confidence: 99%